Perlindungan Hukum Terhadap Eksploitasi Pekerja Anak Dalam Sektor Industri Hiburan - Satryo Sasono; Agus Riwanto; Andina Elok Puri Maharani; Airlangga Suryanegara; Adriana G.Firaussy (CV. Publikasi Indonesia, 2022)
In this case, the entertainment industry is an industrial sector that is very prone to the exploitation of children physically, socially, sexually, and economically. This is because children are recruited and employed on the basis of appearance, work excessively to the point of confiscating children's playing and learning for the material gain of their parents, and sometimes being put in the worst jobs resulting in sexual exploitation due to involvement in prostitution activities. However, there are many factors that make a child forced to work. Child labor is closely related to exploitation, very dangerous work, and hinders education and hinders physical development. This study aims to analyze how forms of legal protection arrangements can make child laborers avoid acts of exploitation, what are the factors that cause the entertainment industry to be prone to child exploitation, and how the government's efforts in tackling child labor in the entertainment industry sector are from acts of exploitation. This study uses the normative legal method or a statutory approach by reviewing all regulations and laws related to and related to the legal issue being studied. The results of this paper state that although there are a number of regulations protecting child labor, the tendency of child labor problems, especially in the entertainment industry sector, has developed in a complex manner towards the worst forms of exploitative work. Disharmonization of regulations and other government efforts related to the handling of child labor is also an influence. Therefore, various ways have been attempted by the government in overcoming this problem, but in fact, it is still not in accordance with what is expected.